2013
DOI: 10.1097/nxn.0b013e318282eala
|View full text |Cite
|
Sign up to set email alerts
|

Using the Omaha System to Describe Health Problems, Interventions, and Outcomes in Home Care in Istanbul, Turkey

Abstract: Preparing nursing students to achieve informatics competencies is essential in today's information-intensive healthcare delivery systems. This study aimed to provide hands-on informatics experience to nursing students and to identify the frequency and type of home care clients' health problems, nursing interventions, and outcomes using a standardized nursing terminology, the Omaha System. Data were collected by 159 nursing students on home visits to 598 clients, who received 8657 interventions from students an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 17 publications
5
65
0
15
Order By: Relevance
“…In the health-related behaviors domain, impairments were most frequently observed in personal care (56.4%), self-feeding and nutrition (15.4%), medication management (12.1%), sleep and rest (10.5%) and physical activity (5.7%). The problems identified in the present study are similar to problems identified in several other studies conducted with individuals receiving home healthcare services [16,20,21,25]. The most common problems identified by Erdogan et al in the health-related behaviors domain were related to personal care, and self-feeding and nutrition [16].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In the health-related behaviors domain, impairments were most frequently observed in personal care (56.4%), self-feeding and nutrition (15.4%), medication management (12.1%), sleep and rest (10.5%) and physical activity (5.7%). The problems identified in the present study are similar to problems identified in several other studies conducted with individuals receiving home healthcare services [16,20,21,25]. The most common problems identified by Erdogan et al in the health-related behaviors domain were related to personal care, and self-feeding and nutrition [16].…”
Section: Discussionsupporting
confidence: 75%
“…As in the present study, the majority of individuals participating in several other studies were elderly people [16,[19][20][21][22]. This situation reveals the necessity of home healthcare services for the elderly in Turkey where the average life expectancy is increasing with each passing day.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations